2020
DOI: 10.31219/osf.io/cf8va
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Virtual Reality Nature Exposure and Test Anxiety

Abstract: The number of students affected by exam anxiety continues to rise. Therefore, it is becoming progressively relevant to explore innovative remediation strategies that will help mitigate the debilitating effects of exam anxiety. The study aimed to investigate whether green environment exposure, delivered by virtual reality (VR) technology, would serve as an effective intervention to mitigate participants’ test anxiety and therefore improve the experience of the exam, measured by positive and negative affect, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 0 publications
0
6
1
Order By: Relevance
“…For instance, the study by Anderson et al [58] has shown that exposure to 360 °videos of nature reduced negative affect in comparison to a control environment. Another study revealed that VR nature exposure improved negative affect in a sample of students who experienced exam anxiety [59]. Contrary to our expectations, there were no significant changes in perceived stress.…”
Section: Discussioncontrasting
confidence: 99%
“…For instance, the study by Anderson et al [58] has shown that exposure to 360 °videos of nature reduced negative affect in comparison to a control environment. Another study revealed that VR nature exposure improved negative affect in a sample of students who experienced exam anxiety [59]. Contrary to our expectations, there were no significant changes in perceived stress.…”
Section: Discussioncontrasting
confidence: 99%
“…(i.e., score equal to 6.5) percentiles, we categorized the studies into "high quality", "medium quality" and "low quality" (Table S3). Fourteen studies were classified as having a high quality (Annerstedt et al, 2013;Blum et al, 2019;Browning, Mimnaugh et al, 2020;Hedblom et al, 2019;Huang et al, 2020;Lakhani et al, 2020;O'meara et al, 2020;Palanica et al, 2019;Rockstroh et al, 2019;Schutte et al, 2017;Sneed et al, 2021;Tabrizian et al, 2018;Wang et al, 2020;Yeo et al, 2020),a further sixteen studies (Anderson et al, 2017;Calogiuri et al, 2018;Chirico, & Gaggioli, 2019;Fleury et al, 2021;Hofman et al, 2021;Lindquist et al, 2020;Liszio, & Masuch, 2019;Liszio et al, 2018;Mattila et al, 2020;Reese et al, 2021;Schebella et al, 2020;Wang et al, 2019;Xiang et al, 2021;Yu et al, 2018;Yu et al, 2020) were classified as having "medium quality", and eight (Burmeister et al, 2018;Evensen et al, 2021;Gao et al, 2019a;2019b;Je, & Lee, 2020;Mostajeran et al, 2021;Pals et al, 2014;van Vliet et al, 2021) as having "low quality". The item in which we found a lower overall score is that on power analysis (pre-or post-hoc) which...…”
Section: Quality Assessmentmentioning
confidence: 99%
“…The effect of virtual nature on positive emotions is inconsistent. A series of studies found that positive emotions did not increase after exposure to virtual nature (Anderson et al, 2017;Gao, Zhang et al, 2019;O'meara et al, 2020). Other studies, however, report significant effects suggesting that exposure to virtual nature was at least no different from exposure to other conditions, such as outdoor nature and biofeedback without VR or no biofeedback (Chirico & Gaggioli, 2019;Rockstroh et al, 2019).…”
Section: Positive Emotionsmentioning
confidence: 99%
“…Whether real or virtual, situations or objects that cause anxiety and fear can be used to affect test anxiety associated with academic achievement, as they can reduce stress and improve cognitive function. The use of 360º video technology can reduce the negative effects of the test experience on students (O'Meara, Cassarino, Bolger, & Setti, 2020). Especially 360-degree video technology, which can be effective in treating psychological problems, can also offer a solution to academic problems such as test anxiety.…”
Section: Introductionmentioning
confidence: 99%